Peter Barlow's insights and contributions to the study of tidal gravity variations and ultra-weak light emissions in plants - Gallep, Cristiano M; Viana, João F; Cifra, Michal; Clarke, Dominic; Robert, Daniel (Annals of botany, 2018)
BACKGROUND: A brief review is given of Peter W. Barlows' contributions to research on gravity tide-related phenomena in plant biology, or 'selenonastic' effects as he called them, including his early research on root growth. Also, new results are presented here from long-term recordings of spontaneous ultra-weak light emission during germination, reinforcing the relationship between local lunisolar tidal acceleration and seedling growth. SCOPE: The main ideas and broad relevance of the work by Barlow and his collaborators about the effects of gravity on plants are reviewed, highlighting the necessity of new models to explain the apparent synchronism between root growth and microscale gravity changes 107 times lower than that exerted by the Earth's gravity. The new results, showing for the first time the germination of coffee beans in sequential tests over 2 months, confirm the co-variation between the patterns in ultra-weak light emission and the lunisolar tidal gravity curves for the initial growth phase. For young sprouts (<1 month old), the rhythm of growth as well as variation in light emission exhibit the once a day and twice a day periodic variations, frequency components that are the hallmark of local lunisolar gravimetric tides. Although present, this pattern is less pronounced in coffee beans older than 1 month. CONCLUSIONS: The apparent co-variation between ultra-weak light emission and growth pattern in coffee seedlings and the lunisolar gravity cycles corroborate those previously found in seedlings from other species. It is proposed here that such patterns may attenuate with time for older sprouts with slow development. These data suggest that new models considering both intra- and intercellular interactions are needed to explain the putative sensing and reaction of seedlings to the variations in the gravimetric tide. Here, a possible model is presented based on supracellular matrix interconnections.
Keywords: Coffea; dějiny 21. století; fyziologie rostlin; gravitace; Gravitation; History, 21st Century; dějiny 20. století; Light; Plant Physiological Phenomena; klíčení; Germination; světlo; History, 20th Century